IMPROVING STUDENTS’ READING ABILITY ON INTRODUCTION TO LINGUISTIC CLASS THROUGH TWO –STAY TWO STRAY (TS-TS) TECHNIQUE - Rijal, Samsi; Rohaniyah, Jaftiyatur (English Education:Journal of English Teaching and Research, 2020)
This research was conducted based on the researcher’s observation in the class of Introduction to Linguistic at second semester of English Education Department Madura Islamic University. From the data, there were some problems of learners, they are; 1) they felt difficult in understanding the subject of Introduction to Linguistic because it was the new subject for them, 2) they were not active in joining the process of teaching and learning. Related to the problems above, the researcher tried to find the solution by choosing the best strategy, it was Cooperative learning TWO –STAY TWO STRAY (TS-TS). This research is CAR (Classroom Action Research) which has four steps: planning, acting, observing and reflecting. The subject of this research was learners of second semester of English Education Department. The result after implementing Cooperative learning TWO –STAY TWO STRAY (TS-TS), there was high motivation from the learners in joining the class and there was a significant improvement of learners’ score from preliminary study, cycle I and Cycle II. In preliminary, there were only 27.3 % learners who got the target of the minimum score, it was 75 (B). In cycle I, there was 63.7 % learners achieved the target and 81.9 % of learners got the target of the research. Based on the data, it could be concluded that this method is success and can be used in teaching reading.